Ozone treatment of meat and meat products: a review - Giménez, Belén; Zaritzky, Noemí; Graiver, Natalia (Frontiers in Food Science and Technology, 2024)
Ozone treatment is a non-thermal method for disinfection; ozone is a powerful oxidizing agent that has been shown to be effective in reducing microbial load, extending the shelf life of meat products. This mini-review covers the analysis of the antimicrobial ozone activity in different meats (beef, poultry, pork, seafood etc.), emphasizing the ozone application methods (liquid or gaseous phase), the applied concentrations and contact times and the effects of ozone treatment on meat quality, safety, and sensory properties. It has been demonstrated that ozone is effective against a broad range of microorganisms, including both Gram-positive and Gram-negative bacteria, spores, and vegetative cells. The efficacy of ozone depends on various factors, such as concentration, type of treatment, temperature, and presence of organic material. Ozone treatment, known for its rapid decomposition and lack of residue, provides an environmentally friendly alternative to traditional chemical sanitizers. Ozone treatments exhibit promising results in enhancing the safety and extending the shelf life of meat products. According to the findings, the application of ozone is an effective technology for prolonging the shelf life of different types of meats and meat products, requiring careful establishment of conditions on a case-by-case basis.